O ENSINO DA GEOMETRIA NOS ANOS INICIAIS: UM ESTUDO DE CASO COM A TUTORA E AS CURSISTAS DO PROGRAMA PRÓ-LETRAMENTO EM SANTIAGO/RS - Cardoso, Franciele C.; Soares, Maria A. d. S. (Salão do Conhecimento, 2013)
Resumo